PATIENT FOCUSED DRUG DEVELOPMENT – SCOPE, IMPORTANCE CHALLENGES AND REGULATORY INITIATIVES - Tomanović, Mirjana (Archives of Pharmacy, 2023)
Through its history, regulatory science has grown and expanded to adapt to the emergence of new needs and requirements. The partnership of health authorities with companies working on discovery and development of medicinal products has for years been reshaping each other and regulatory sciences. More recently, attitudes towards patient involvement in drug development have changed significantly. Traditionally, healthcare stakeholders (health technology assessment (HTA) bodies, regulatory authorities, industry, academia) thought of patients mostly as clinical trial participants with their contribution limited to data provision. However, the drug development paradigm is shifting to deliver medicines that patients truly value. It is now recognised that improved patient involvement can drive the development of innovative medicines that deliver more relevant and impactful patient outcomes and help make medicine development faster, more efficient, and more valuable. It can lead to better prioritisation of early research, improved resource allocation and trial designs that better reflect patient needs by addressing potential barriers to patient participation and enhancing recruitment and retention. With patient involvement in drug development expanding, we are witnessing the emergence of regulatory initiatives aimed at facilitating patient engagement (PE). Strengthening patient relevance in evidence generation was identified as a key priority for the health authorities, with initiatives such as Patient-Focused Drug Development – PFDD by FDA (PFDD Guidance Series for Enhancing the Incorporation of the Patient’s Voice in Medical Product Development and Regulatory Decision Making), and the EMA multi-stakeholder workshops on patient engagement data (PED).